The Role of UNCLOS 1982 in Maintaining and Protecting the International Marine Environment - Kusuma, Anita Dian Eka; Putra, Akbar Kurnia (Lampung Journal of International Law, 2024)
The disposal of nuclear waste into the Sea of Japan is a complex and contentious issue that intertwines international law and environmental concerns. Japan, a major producer of nuclear waste, faces international pressure to manage this waste according to global legal and environmental standards. The United Nations Convention on the Law of the Sea (UNCLOS) provides a framework for managing marine resources, including waste disposal, but ambiguities in the law complicate the definition of state responsibilities. From an environmental perspective, the disposal of nuclear waste could have long-lasting detrimental impacts on marine ecosystems and human health, emphasizing the need for sustainability in decision-making processes. Moreover, international conventions like the Espoo Convention and the Aarhus Convention stress the importance of public participation in environmental governance, advocating for civil society's involvement to ensure public interests and concerns are addressed. This research aims to analyze Japan's disposal actions and explore the role of UNCLOS 1982 in protecting the international marine environment, using a normative juridical approach to examine legal conflicts, gaps, and ambiguous norms.